2021
DOI: 10.3347/kjp.2021.59.6.557
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Macrophages in Proliferation of Prostate Cancer Cells Infected with Trichomonas vaginalis

Abstract: Macrophages play a key role in chronic inflammation, and are the most abundant immune cells in the tumor microenvironment. We investigated whether an interaction between inflamed prostate cancer cells stimulated with Trichomonas vaginalis and macrophages stimulates the proliferation of the cancer cells. Conditioned medium was prepared from T. vaginalis-infected (TCM) and uninfected (CM) mouse prostate cancer (PCa) cell line (TRAMP-C2 cells). Thereafter conditioned medium was prepared from macrophages (J774A.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…We studied the changes in the immune genome profile in primary ESCA and uncovered its possible underlying molecular mechanisms. The KEEG analysis revealed that these IRGs were enriched in the cytokine-cytokine receptor interaction pathway, which reflects previous findings that these pathways play a crucial role in the proliferation, immune responses, and progression in several cancers (24)(25)(26). The dysregulation of cytokine interactions is also involved in the pathogenesis of ESCA (27).…”
Section: Discussionsupporting
confidence: 82%
“…We studied the changes in the immune genome profile in primary ESCA and uncovered its possible underlying molecular mechanisms. The KEEG analysis revealed that these IRGs were enriched in the cytokine-cytokine receptor interaction pathway, which reflects previous findings that these pathways play a crucial role in the proliferation, immune responses, and progression in several cancers (24)(25)(26). The dysregulation of cytokine interactions is also involved in the pathogenesis of ESCA (27).…”
Section: Discussionsupporting
confidence: 82%
“…production following infection (Han et al, 2020), leading to the polarization of M2 macrophages, and progression of neoplastic cells and greater neoplasm aggressiveness (Han et al, 2020;Chung et al, 2020). The study findings also indicate that PC cells show greater sensitivity to T. vaginalis compared with healthy prostatic epithelium (Kushwaha et al, 2020), leading to an exacerbation of PC through an inflammatory process caused by T. vaginalis that can lead to metaplasia (Kim et al, 2021a).…”
Section: In Vitro Studiesmentioning
confidence: 74%
“…These results demonstrate that T. vaginalis induces an inflammatory response in PCa cells in vitro and in vivo in mouse models, which accelerates the proliferation of PCa cells. Similar to how T. vaginalis infection causes PCa cells to become inflamed, these chemokines (CXCL1, CXCR2) cause macrophages to migrate and become activated [ 158 ].…”
Section: Chemokines/cxcrs and Pcamentioning
confidence: 99%